(untitled) (Texas Journal of Medical Science, 2023)
The investigation into the involvement of vitamin D in the pathogenesis and prevention of type 2 diabetes has garnered widespread scholarly attention. Notably, vitamin D receptors are discernible in pancreatic beta cells and immune cells. In addition to its established function as the primary regulator of calcium absorption, vitamin D exerts influence on the activity of calcium-associated endopeptidases in beta cells, facilitating the conversion of proinsulin to insulin and augmenting insulin production. Within peripheral insulin target tissues, vitamin D governs insulin action through the modulation of calcium homeostasis. Further, vitamin D exhibits pronounced immunosuppressive properties. Noteworthy is the potential implication of vitamin D deficiency in the etiology of type 2 diabetes, manifesting in the inhibition of insulin secretion and enhancement of glucose tolerance. The article underscores the imperative for comprehensive research and clinical trials elucidating the multifaceted roles of vitamin D and calcium in maintaining a robust physiological framework. Insightful findings from studies conducted in Uzbekistan and globally underscore a prevailing inadequacy in the dietary intake of calcium and vitamin D among diverse populations, taking into account geographical, ethnic, and physiological variances. Emphasis is placed on the critical significance of sustaining optimal levels of calcium and vitamin D for skeletal health, particularly in the context of osteoporosis prevention and treatment.